Open notes in psychotherapy: An exploratory mixed methods survey of psychotherapy students in Switzerland - Anna Kharko; Sarah Buergler; Annika Bärkås; Maria Hägglund; Jens Gaab; Asbjørn Johansen Fagerlund; Cosima Locher; Charlotte Blease (Digital Health, 2024)
Background In a growing number of countries, patients are offered access to their full online clinical records, including the narrative reports written by clinicians (the latter, referred to as “open notes”). Even in countries with mature patient online record access, access to psychotherapy notes is not mandatory. To date, no research has explored the views of psychotherapy trainees about open notes. Objective This study aimed to explore the opinions of psychotherapy trainees in Switzerland about patients’ access to psychotherapists’ free-text summaries. Methods We administered a web-based mixed methods survey to 201 psychotherapy trainees to explore their familiarity with and opinions about the impact on patients and psychotherapy practice of offering patients online access to their psychotherapy notes. Descriptive statistics were used to analyze the 42-item survey, and qualitative descriptive analysis was employed to examine written responses to four open-ended questions. Results Seventy-two (35.8%) trainees completed the survey. Quantitative results revealed mixed views about open notes. 75% agreed that, in general open notes were a good idea, and 94.1% agreed that education about open notes should be part of psychotherapy training. When considering impact on patients and psychotherapy, four themes emerged: (a) negative impact on therapy; (b) positive impact on therapy; (c) impact on patients; and (d) documentation. Students identified concerns related to increase in workload, harm to the psychotherapeutic relationship, and compromised quality of records. They also identified many potential benefits including better patient communication and informed consent processes. In describing impact on different therapy types, students believed that open notes might have differential impact depending on the psychotherapy approaches. Conclusions Sharing psychotherapy notes is not routine but is likely to expand. This mixed methods study provides timely insights into the views of psychotherapy trainees regarding the impact of open notes on patient care and psychotherapy practice.